Avós que detêm a guarda judicial dos netos: que lugar é esse? - Albuquerque, Karlise Maranhão Lucena de (2018)
The increasing life expectancy has provided an extension between different generations of the same family, favoring a greater interaction between grandparents and grandchildren. It is known that grandparents have already raised their grandchildren, without proven legal dependence, for many years, however, recently, there has been an increase in demand for grandparents in accessing Judiciary to regularize this situation, in reason of the need of a legal guardian, for various purposes. Therefore, the present work was carried out to investigate, from the perspective of the grandmothers, the place occupied by them, within the family context, after deferring judicial custody of their grandchildren. Specifically, it was intended to analyze the factors that propelled grandmothers to take care of their grandchildren, as well as to characterize their feelings and needs, from the transfer of the duties of the biological countries to the grandparents, in addition to a framework as a family structure after obtaining custody, identifying the gains and difficulties arising from this situation, and also describe the changes that a legal custody had in the lives of the grandparents, with this new legal situation. It is a research of qualitative nature in which 5 grandmothers take full-time care of grandchildren, aged between 42-64 years, of low socio-economic levels, residing in the metropolitan area of Recife and who have the legal document of guard of their grandchildren. The research was approved by the Judge of the First Court of Childhood and Youth of Recife. Initially, an analysis was made of the documents referring to the records of the selected families' cases, from the years 2013 to 2015, in order to analyze the initial petitions and technical opinions built by the professionals who work in the First Ward of Children and Youth of the region of Recife, in the Nucleus NIAP (Integrated Nucleus of Psychosocial Counseling). In a second moment, a Field Survey was carried out, where a socio-demographic questionnaire was used and an interview conducted semi-directed from a previously defined script, being analyzed according to the Thematic Content Analysis Technique. The data obtained in the present study show that as grandparents they came to replace deceased, chemical dependent or negligent parents. The grandchildren were raised mainly by the grandparents because, in most cases, they were already responsible for the children from birth. The reason that made the grandparents look for the Judiciary was the absence of the parents, however, what prompted the grandparents to activate the Justice System was the fear that their grandchildren were withdrawn from their lives, since there was no legal evidence of their care. It was also evident, in spite of the satisfaction in the coexistence with the grandchildren, there is an affective ambivalence when they are occupying the parental place, ceasing to be "simply grandmothers". They assume a very high responsibility burden, mainly because this charge is legitimized by a Power that goes beyond the family sphere. It is hoped to be able to contribute to broaden the understanding and visibility of this familiar configuration, as well as to provide subsidies for the work of professionals who deal with family members.